Xylophagia (paper eating): A rare form of pica. Issue 12 (15th July 2020) - Kurtz, Daniel; Azar, Ibrahim; Khan, Hajra; Lilley, Kirthi; Woldie, Indryas
Abstract: Xylophagia is a form of pica where patients have the unusual craving for ingestion of paper. After treating the underlying cause of pica, in this case treating iron deficiency anemia with iron replacement therapy, these unusual cravings resolve. Abstract : Xylophagia is a form of pica where patients have the unusual craving for ingestion of paper. After treating the underlying cause of pica, in this case treating iron deficiency anemia with iron replacement therapy, these unusual cravings resolve.